Intravesical Gemcitabine versus Intravesical Bacillus Calmette-Guerin for the Treatment of Intermediate-Risk Non-Muscle Invasive Bladder Cancer: A Randomized Controlled Trial - Ansari Djafari, Anahita; Javanmard, Babak; Razzaghi, Mohammadreza; Hojjati, Seyyed Ali; Razzaghi, Zahra; Faraji, Saba; Rahavian, Amirhossein; Garoosi, Maryam (Urology Journal, 2023)
Purpose: The most common adjuvant therapy known for non-invasive muscle bladder cancer (NMIBC) is intravesical Bacillus Calmette-Guerin (BCG). Intravesical chemotherapy drugs like gemcitabine can also be used post-TURBT, which is considered as a good alternative for BCG, or can be used as a second-line treatment. Due to the common side effects of BCG, the use of chemotherapy drugs as intravesical treatments is currently increasing. Materials and Methods: 117 intermediate-risk NMIBC cases were included in this study. All the patients underwent TURBT surgery and received 1 gr intravesical gemcitabine immediately after performing the surgery. The patients were then divided into two groups, either receiving intravesical gemcitabine or intravesical BCG weekly for 6 weeks. The patients were followed up with cystoscopy. Results: Most patients were men who had smoking risk factors. The youngest patient was 36 years old and the oldest one was 88 years old. The rate of side effects in the group receiving gemcitabine (13.6%) was much lower than the group receiving BCG (44.8%). (P-value = 0.016). The recurrence rate during a one year period was lower in the group consisting of patients receiving gemcitabine compared to the group receiving BCG (19 patients vs. 23 patients) (p-value = 0.401) Conclusion: The efficacy of intravesical gemcitabine and intravesical BCG was almost equal in the treatment of intermediate-risk NMIBCs. The adverse effects of gemcitabine were found to be significantly lower than BCG. Due to causing fewer complications, gemcitabine can be known as a good alternative, especially among elderly patients with comorbidities.